Bryman's social research methods - Clark, Tom (Lecturer in research methods); Foster, Liam; Sloan, Luke; Bryman, Alan; Bryman, Alan. (Oxford : Oxford University Press, 2021)
Clear, comprehensive, and trusted, Bryman's Social Research Methods has supported over a quarter of a million students through their research methods course and research project. Spanning theory and practice and covering quantitative, qualitative, and mixed methods, this bestselling text offers unrivalled coverage of the whole research process. The authors have worked closely with lecturers and students in thoroughly updating the sixth edition to reflect the current social science landscape, and carefully streamlining content to make it relevant and appealing to today's students. As a result, the text's comprehensive coverage - which includes many new examples and additional material on areas such as social media research and big data - is now even clearer, more focused, and easier to navigate. In addition to many new examples of published research, this edition features the insights of a panel of recent graduates from their experiences of researching a variety of fascinating topics, including attitudes towards the LGBT+ community on social media, the experiences of Pakistani Muslim single mothers, and the impact of screen time on sleep. 'Learn from experience' boxes in every chapter contain their candid reflections on the successes and challenges of their projects, and their advice for student researchers. --
Previous edition: as by Alan Bryman, 2016.
Includes bibliographical references and indexes.
Keywords: Social sciences -- Research; Social sciences -- Methodology; Social research; Research methods; Social sciences -- Research -- Methodology